Validity and Reliability of the Treatment Adherence Questionnaire for Patients with Hypertension - Esquivel Garzón, Natalia; Díaz Heredia, Luz Patricia (Investigación y Educación en Enfermería, 2019)
Objective. To determine the validity and reliability of the Treatment Adherence Questionnaire for Patients with Hypertension (TAQPH), Spanish version, designed by Chunhua Ma et al. Methods. This study was carried out in the city of Ibagué (Colombia) and the test validation determined validity (face, content, and construct) and reliability. Face and content validity were conducted through expert judgment, using Fleiss’ Kappa Coefficient statistical tests and modified Lawshe’s content validity index. The construct validity and the reliability test had the participation of 220 people with diagnosis of primary hypertension. Reliability was calculated through Cronbach’s alpha statistical test. Results. In the face validity, the instrument reported a Fleiss’ Kappa index was 0.68 in comprehension, 0.76 in clarity, and 0.64 in accuracy, interpreted as a substantial agreement. The content validity index was satisfactory with 0.91; el exploratory factor analysis reported six factors with a total variance explained of 54%. Cronbach’s alpha for the total scale was 0.74. Conclusion. The Spanish version of the TAQPH is a valid and reliable scale to evaluate adherence to treatment in patients with primary hypertension. How to cite this article: Esquivel N, Díaz LP. Validity and Reliability of the Treatment Adherence Questionnaire for Patients with Hypertension. Invest. Educ. Enferm. 2019; 37(3):e09.